A modified optimal orthogonal new additive model. Issue 22 (16th November 2016) - Singh, Housila P.; Tarray, Tanveer A.
ABSTRACT: In this article, a new randomized response model has been proposed. The proposed model is found to be more efficient than the randomized response models studied by Singh (2010 ). The relative efficiency of the proposed model has been studied with respect to the Singh (2010 ) model. Numerical illustrations are also given in support of the present study.